2010
DOI: 10.1007/s11357-010-9157-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced protein repair and recycling are not correlated with longevity in 15 vertebrate endotherm species

Abstract: Previous studies have shown that longevity is associated with enhanced cellular stress resistance. This observation supports the disposable soma theory of aging, which suggests that the investment made in cellular maintenance will be proportional to selective pressures to extend lifespan. Maintenance of protein homeostasis is a critical component of cellular maintenance and stress resistance. To test the hypothesis that enhanced protein repair and recycling activities underlie longevity, we measured the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 52 publications
(66 reference statements)
2
43
0
Order By: Relevance
“…Some of the main themes of this study seem to be largely confirmatory and applicable to most chronic conditions where patients value well-resourced services [8,12,16,17], good social support [1,5,16,17,18] and medical insurance that covers the diagnostic process [11].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Some of the main themes of this study seem to be largely confirmatory and applicable to most chronic conditions where patients value well-resourced services [8,12,16,17], good social support [1,5,16,17,18] and medical insurance that covers the diagnostic process [11].…”
Section: Discussionmentioning
confidence: 76%
“…PNES is a complex and controversial disorder that remains poorly understood and managed in the clinical setting [2]. Nevertheless, PNES is a common neuropsychiatric condition which is often misdiagnosed as ES due to the similarities in presentation, frequently resulting in prolonged treatment with anti-epileptic drugs (AED), and avoided by many healthcare providers [1,3,4,5]. Associated stigma and loss of quality of life are compound consequences of misdiagnosis [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the rate at which macromolecular oxidative damage (to both proteins and DNA) occurs probably decreases with increasing body mass, and therefore the rates of recycling/repair required to maintain cellular homeostasis and viability are concomitantly reduced. An important caveat, however, is that both protein (Salway et al 2011) and DNA homeostasis activities were measured under non-stressed conditions, so we cannot detect any differences in the inducibility of these activities that might exist between species and be related to MLSP. Another concept critical to the interpretation of the data in this study is that relationships between BER (or other DNA repair activities) and lifespan may be highly cell-type specific.…”
Section: Discussionmentioning
confidence: 97%
“…Salway et al (2011) showed that the 20S/26S proteasome, as well as the activities of enzymes capable of maintaining the redox state of proteins, generally correlate negatively with species body mass but show no relationship with MLSP. This suggests that the rate at which macromolecular oxidative damage (to both proteins and DNA) occurs probably decreases with increasing body mass, and therefore the rates of recycling/repair required to maintain cellular homeostasis and viability are concomitantly reduced.…”
Section: Discussionmentioning
confidence: 99%